SOSIALISASI PERILAKU HIDUP BERSIH DAN SEHAT DENGAN PENCEGAHAN DAN PENGOBATAN SARIAWAN - Putri, Fatya Kamila; Nurfatimah, Baiq Aluh; Suhayatman, Early Windary; Rizkika, Adila (Universitas Mataram, 2024)
Aphtose stomatitis is an inflammatory disease that often occurs in the oral cavity. Thrush can usually be in the form of single or group spots that are yellowish white in color with a concave surface. The purpose of this activity is to increase health knowledge in students of SD Negeri 2 Terong Tawah through education on the prevention and treatment of thrush and can change health behavior in children of SDN 2 Terong Tawah in a better direction. Knowledge improvement is done by socialization and pre test - post test system. The results of written evaluations in the form of pre tests and post tests obtained a value with an average of 64.58 Â± 16.14 otherwise after being given material exposure, some students experienced an increase and the average post test value obtained was 85 Â± 8.84. This activity can increase knowledge about health in students of SD Negeri 2 Terong Tawah through education on the prevention and treatment of thrush.